(untitled) (Philological Studies, 2019)
The subject of this paper is adultery in Roman law, which was considered as lawful cause (iusta causa) for unilateral divorce in all periods of Roman legal history. After his accession, Augustus enacted the lex Iulia de adulteriis coercendis (18 BC) whereby divorce was made obligatory in the case of adultery. Since then, adultery was not only moral offence, but crime (crimen, ἔγκλημα), which was penalized by the state. Hence, adultery was not res privata but res publica, and continued to be regarded as such even in the legislations of Christian Emperors. Anyhow, there are fundamental differences between pre- Christian and Christian legislation concerning adultery and marriage, which are to be analyzed in the following text. Finally, I give explanation to the words adulterium and repudium, and correlate them with equivalents in Macedonian language in order to explain the nature of Roman law and Roman view on adultery.